(untitled) (Scientific journal of the Fergana State University, 2023)
Interactive methods are methods used by a teacher to teach students in accordance with the requirements of the time. Our article presents a number of methods (concerning the consolidation of theoretical knowledge, the formation of students’ consciousness, solving problem situations)on the use of interactive methods in practical classes on the natural geography of continents and oceans in the 7th grade. These methods serve to consolidate both theoretical and practical knowledge of schoolchildren as a result of their application.